PERBANDINGAN MOTIF DAN KEPUASAN ANAK MUDA KOTA DENPASAR MENGGUNAKAN RINSTAGRAM DAN FINSTAGRAM - Putri, Saras Pillary; Dewi Pascarani, Ni Nyoman; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
aABSTRACTt Thisi study aimed to find,i out what are the motives and satisfaction of youth ini Denpasar in using Rinstagram and Finstagram. Denpasar city was chosen because it was recorded as the city of the most internet users in the Province lof, Bali.The media consumption motives used in this study is the motive put forward by Papacharissi and Rubin using the Uses, and Gratifications, Theory. This research, used descriptive quantitative method with the sampling technique is purposive sampling which is analyzed using descriptive statistics by looking at the average score of motives and satisfaction.The results showed that there were three motives that can be satisfied in using Rinstagram that is the motif of filling leisure time, seeking information, comfort motive. Then there, are four motives, that, can be satisfied in using Finstagram, that is, the usability, information seeking, comfort, entertainment motive. The main reason for using Finstagram is to stalk someone. Keywords: Finstagram, Motives, Rinstagram, Satisfaction